Pelatihan Kreativitas dan Tanggung Jawab Santri melalui Kegiatan Kerajinan Tangan (Soft Skill) di Maahad Tahfiz Arabic Al-Gontory Lil Banat Selangor Malaysia - Ismail Mustaqim; Raharjo Raharjo; Herlina Herlina; Riyanto Riyanto; Amie Primarnie; Alvina Chaerunniza Zumida; Khairunnisa Khairunnisa; Nurariana Ayu Wardani; Tya Sulistiyani; Marzul Fuardi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Soft skill development is an essential part of pesantren education, aiming to foster creativity, independence, and teamwork among students. One of the implementations of this development was carried out through a handicraft program using simple materials such as ice cream sticks, flannel fabric, hot glue, candles, lighters, and additional decorative items. This program was carried out by the national PKM IAI team from Bogor at Maahad Tahfiz Arabic Al Gontory Lil Banat, involving 45 students divided into 10 groups, each consisting of 4–5 members. The activity was implemented within 90 minutes of crafting time, followed by a 5-minute presentation session for each group to showcase their work. The results of the activity showed that the students were able to produce various creative handicrafts with aesthetic value by utilizing simple materials. Moreover, this program successfully enhanced students’ teamwork, creativity, and communication skills through group discussions and presentations. It also increased their confidence in presenting their work in front of peers. Therefore, handicraft activities not only foster creativity but also serve as an effective medium for developing soft skills that are highly relevant to students’ future lives.